2020
DOI: 10.1111/ejn.14870
|View full text |Cite
|
Sign up to set email alerts
|

New insight into Parkinson’s disease‐related impairment of the automatic control of upright stance

Abstract: Parkinson's disease (PD) affects the automatic control of body movements. In our study, we tested PD-related impairments in automatic postural control in quiet upright stance. Twenty PD patients (mean age: 60 ± 8 years; Hoehn and Yahr: 2.00 ± 0.32, on-drug) and twenty age-matched controls (61 ± 7 years) were recruited. We studied interrelations between center-of-pressure movements, body movements (head, neck, and lower back), eye movements and variability of pupil size. Participants performed two fixation task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Accordingly, external visuospatial cues can be used to compensate for visuospatial processing deficits in PD patients, especially in complex or novel environments. Note that a recent study ( Bonnet et al, 2020 ) reported reduced automatic visuomotor coupling and increased attentional demands to maintain standard posture in the presence of distracting stimuli, which was shown to induce episodes of falling or FoG in PD patients.…”
Section: Task-based Imaging Studies Of Fog In Parkinson’s Diseasementioning
confidence: 94%
“…Accordingly, external visuospatial cues can be used to compensate for visuospatial processing deficits in PD patients, especially in complex or novel environments. Note that a recent study ( Bonnet et al, 2020 ) reported reduced automatic visuomotor coupling and increased attentional demands to maintain standard posture in the presence of distracting stimuli, which was shown to induce episodes of falling or FoG in PD patients.…”
Section: Task-based Imaging Studies Of Fog In Parkinson’s Diseasementioning
confidence: 94%